Fatal Necrotizing Encephalopathy after Treatment with Nivolumab for Squamous Non-Small Cell Lung Cancer: Case Report and Review of the Literature - Leitinger, Markus; Varosanec, Mihael V.; Pikija, Slaven; Wass, Romana E.; Bandke, Dave; Weis, Serge; Studnicka, Michael; Grinzinger, Susanne; McCoy, Mark R.; Hauer, Larissa; Sellner, Johann (Frontiers in Immunology, 2018)
Immune checkpoint inhibitors are antibodies which enhance cellular and humoral immune responses and are approved for the treatment of various tumors. Immune-related adverse events (irAE) involving different organs and systems are, however, among the side-effects. Recent reports of severe persistent neurological deficits and even fatal cases underpin the need for better understanding of the exact pathomechanisms of central nervous system (CNS) toxicity. To our knowledge, we report the first biopsy-proven case of fatal necrotizing encephalopathy after treatment with nivolumab. Nivolumab targets the immune-check point inhibitor programmed cell death-1 and was used for squamous non-small cell lung cancer. Partly reversible neurologic and psychiatric symptoms and unremarkable brain MRI were observed after the first course. Neurological symptoms progressed and recurrent seizures developed after the second course. Brain MRI disclosed multiple edematous and confluent supra- and infratentorial lesions, partly with contrast-enhancement. We excluded autoimmune and paraneoplastic causes, and performed ancillary investigations to rule out common and opportunistic infections. Eventually, post-mortem histopathological analysis of the brain revealed a necrotizing process, which contrasts previous cases reporting parenchymal immune cell infiltration or demyelination. Appropriate diagnostic pathways and treatment algorithms need to be implemented for the work-up of CNS toxicity and irAEs related to immune checkpoint inhibitor treatment.